Effect of Ron Increase in Molasses Gasoline-Bioethanol Mixture on 4-Stroke Gasoline Engine Performance - Winoko, Yuniarto Agus; Azhari, Rizky Kharisma (International Journal of Marine Engineering Innovation and Research, 2024)
The development of technology in the 4.0 era has led to higher energy consumption. Meanwhile, Indonesia's energy consumption has been increasing every year. This requires the substitution of alternative energy vehicle fuels. One of them is bioethanol. Bioethanol can be obtained from plants, namely molasses. The use of RON enhancers can increase the octane rating so that low quality fuel can be used. By using high octane, the performance and fuel consumption will be optimal. The purpose of this study was to determine the performance of a 4-stroke petrol engine. This research uses an experimental approach where direct experiments are carried out on torque, power and fuel consumption. The data obtained is also presented graphically. In this study, the independent variables used were Ron enhancers with masses of 0ml, 5ml, 10ml, 15ml and molasses bioethanol percentages of 0%, 10%, 15%, 20%. Control variables engine speed 5500 rpm to 9000 rpm. The highest power results were obtained with a mixture of 0% bioethanol and 5ml RON enhancer, 7.90hp at 8000 rpm. The highest torque is achieved with a mixture of 0% bioethanol and 15ml RON enhancer 8.74 Nm at 6000 rpm. For fuel consumption, the 15% bioethanol mixture with the addition of 0ml RON enhancer is the lowest at 0.0804 kg/Hp.hour at 6000 rpm.